Impacts of engineered nanoparticles and antibiotics on denitrification: Element cycling functional genes and antibiotic resistance genes - Zhang, Ruijie; Xuming Xu; Yitao Lyu; Ying Zhou; Qian Chen; Sun, Weiling (Ecotoxicology and Environmental SafetyEcotoxicology and Environmental Safety, 2022)
The wide presence of antibiotics and minerals warrants their combined effects on the denitrification in natural aquatic environment. Herein, we investigated the effects of two antibiotics, sulfamethazine (SMZ) and chlortetracycline (CTC), on the reduction of NO3--N and accumulation of NO2--N in the absence and presence of engineered nanoparticles (NPs) (Al2O3, SiO2, and geothite) using 16 S rRNA sequencing and high-throughput quantitative PCR. The results showed that the addition of antibiotics inhibited the reduction of NO3--N by changing the bacterial community structure and reducing the abundance of denitrification genes, while engineered NPs promoted the denitrification by increasing the abundance of denitrification genes. In the binary systems, engineered NPs alleviated the inhibitory effect of antibiotics through enriching the denitrification genes and adsorbing antibiotics. Antibiotics and its combination with engineered NPs changed the composition of functional genes related to C, N, P, S metabolisms (p < 0.01). The addition of antibiotics and/or engineered NPs altered the bacterial community structure, which is dominated by the genera of Enterobacter (40.7-90.5%), Bacillus (4.9-58.5%), and Pseudomonas (0.21-12.7%). The significant relationship between denitrification, carbon metabolism genes, and antibiotic resistance genes revealed that the heterotrophic denitrifying bacteria may host the antibiotic resistance genes and denitrification genes simultaneously. The findings underscore the significance of engineered NPs in the toxicity assessment of pollutants, and provide a more realistic insight into the toxicity of antibiotics in the natural aquatic environment.